Nursing education: strategic planning highlighted (Research, Society and Development, 2020)
Strategic planning can be defined as a set of actions established in order for the outlined objectives to be achieved. In this article the importance of the nurse in carrying out the principles of management and administration in his work routine will be pointed out. The general objective of the study was to evaluate and correlate the acceptability of students in the face of strategic planning, through an educational workshop and, as a final proposal, to develop a free course so that health professionals, especially nurses, can deepen their knowledge on this subject. This is an articulation of the teaching practice between the stricto sensu postgraduate program and the nursing graduate program, through strategic health planning. The understanding of the 5th year undergraduate nursing students at the University Center of Volta Redonda about strategic planning was investigated, and their engagement in the educational workshop. The methodology used was data collection. Initially, a pre-test (questionnaire) was used and with the answers produced by the students, it was possible to make the educational workshop closer to everyone’s reality. The evaluation of students regarding the workshop’s exercise was considered satisfactory. The results showed that the activities practiced in the workshop had good adherence and the students obtained the expected understanding. This workshop contributes to motivate students to assume management positions through strategic planning appropriate to the work institution. It was also concluded that the teaching method applied in the workshop facilitated the clarification of doubts, the visualization and understanding of the content.